2005
DOI: 10.1021/jf051390h
|View full text |Cite
|
Sign up to set email alerts
|

Puerins A and B, Two New 8-C Substituted Flavan-3-ols from Pu-er Tea

Abstract: Pu-er tea is a special treated fermented tea produced from crude green tea, which is prepared from the leaves of Camellia sinensis var. assamica. It is a traditional beverage having been used in China, particularly the southern areas, for a long time. Chemical investigation led to the identification of two new 8-C substituted flavan-3-ols, puerins A (1) and B (2), and two known cinchonain-type phenols, epicatechin-[7,8-bc]-4alpha-(4-hydroxyphenyl)-dihydro-2(3H)-pyranone (3) and cinchonain Ib (4), together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 10 publications
1
67
0
Order By: Relevance
“…In contrast, the post-fermented teas are produced by 4 aerobic or anaerobic microbial fermentation of heat-processed green tea leaves (Gong, Watanabe, Yagi, Etoh, Sakata, Ina, & Liu, 1993;Okada, Takahashi, Ohara, Uchimura, & Kozaki, 1996). During the fermentation process, the levels of tea catechins decrease because of decomposition by microbial enzymes and autoxidation; however, only a few catechin metabolites characteristic to post-fermented tea have been reported (Zhou, Zhang, Xu, & Yang, 2005). Thus we have examined the chemical constituents of a commercially available post-fermented tea product.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the post-fermented teas are produced by 4 aerobic or anaerobic microbial fermentation of heat-processed green tea leaves (Gong, Watanabe, Yagi, Etoh, Sakata, Ina, & Liu, 1993;Okada, Takahashi, Ohara, Uchimura, & Kozaki, 1996). During the fermentation process, the levels of tea catechins decrease because of decomposition by microbial enzymes and autoxidation; however, only a few catechin metabolites characteristic to post-fermented tea have been reported (Zhou, Zhang, Xu, & Yang, 2005). Thus we have examined the chemical constituents of a commercially available post-fermented tea product.…”
Section: Introductionmentioning
confidence: 99%
“…Pu'er tea is produced by a microbial fermentation of black tea. Some novel compounds have been isolated and it is suggested that they form during the fermentation (Zhou et al 2005). These include two new 8-C substituted flavan-3-ols, puerins A and B, and two known cinchonain-type phenols, epicatechin-[7,8-bc]-4-(4-hydroxyphenyl)-dihydro-2(3H)-pyranone and cinchonain Ib, and 2,2 ,6,6 -tetrahydroxydiphenyl (Figure 7.56).…”
mentioning
confidence: 99%
“…Plums [131,178], sorghum [88], potatoes [76,124], mangos [124,179,180], kernels [138], cherries [13, 42,43,181], spinach [124,156,182], kale [183], broccoli [124,145], cabbage [55], asparagus [156], lettuces [124], oranges [124], arugulas [137], tea [184], artichokes [132], coffee [185], honey [133,186], apricots [187], citrus fruits [136], oranges [142], bush butter fruits [188], radishes [156,189], cabbages [156,124], pepper [156], olive oil [85,190], cowpeas [104], cactus pears [191], Kancolla seeds [192], Pinto beans [193], beans [82], soybeans [99], and lentils [82].…”
Section: Food Sourcementioning
confidence: 99%
“…The major flavonol that occurred in Pu-er tea (a treated fermented tea produced from crude green tea prepared from the leaves of Camellia sinensis) is myricetin [184].…”
Section: Structures Of Individual Compounds Content and Changes In Cmentioning
confidence: 99%